Case finding of dry eye disease in Norwegian optometric practice: a cross-sectional study - Ystenæs, Ann Elisabeth; Sand, Ingeborg; Sundling, Vibeke (Scandinavian Journal of Optometry and Visual Science, 2021)
Optometrists are primary eye care providers, and it is essential that they efficiently identify patients who will benefit from dry eye management. The aim of the study was to explore case finding of dry eye disease (DED) in optometric practice. A cross-sectional study examining dry eye symptoms and signs in 186 patients (18–70 years of age) attending a routine eye examination, with DED defined according to the criteria of the Tear Film and Ocular Surface Society Dry Eye Workshop II. Standard statistical tests were used, and clinical diagnostics were explored using sensitivity, specificity, and receiveroperating curve (ROC) statistics. Fifty-six patients were contact lens wearers, and they were significantly younger than the non-contact lens wearers (mean age 35 (SD = 1) versus 48 (± 2) years). The mean best corrected visual acuity (BCVA) in the better eye was 1.0 (± 0.1) (decimal acuity). There was no difference in BCVA between contact lens wearers and non-contact lens wearers. The mean Ocular Surface Disease Index (OSDI) score was 22 (± 19), and 138 patients had at least one positive homeostasis marker. Eighty-six had DED, 52 had signs without symptoms, and 23 had symptoms without signs of DED. The sensitivity and specificity of OSDI in detecting any positive homeostasis marker were 62% and 54%, respectively. In all, 106 patients had meibomian gland dysfunction (MGD), of which 49 were asymptomatic. In a ROC analysis, an OSDI ≥ 13 showed a diagnostic ability to differentiate between patients with a fluorescein breakup time (FBUT) < 10 seconds and a fluorescein breakup time ≥ 10 seconds, but not between patients with and without staining or MGD. The majority of patients had dry eye signs and/or dry eye symptoms. Routine assessment of FBUT and meibomian glands may enable case finding of DED in optometric practice.